Interferon regulatory factor 9 protects against hepatic insulin resistance and steatosis in male mice - Wang, Xin-An (2013)
Obesity is a calorie excessive state that is associated with high risk of diabetes, atherosclerosis and certain types of tumors. Obesity may induce inflammation and insulin resistance. We found that the expression of interferon regulatory factor 9 (IRF9), a major transcription factor mediating interferon (IFN) responses, was lower in the livers of obese mice than in those of their lean counterparts. Furthermore, whole-body IRF9 knockout (KO) mice were more obese and had aggravated insulin resistance, hepatic steatosis and inflammation after chronic high-fat diet (HFD) feeding. In contrast, adenoviral-mediated hepatic IRF9 overexpression in both diet-induced and genetically (ob/ob) obese mice showed markedly improved hepatic insulin sensitivity and attenuated hepatic steatosis and inflammation. We further employed a yeast two-hybrid screening system to investigate the interactions between IRF9 and its cofactors. Importantly, we identified that IRF9 interacts with peroxisome proliferator-activated receptor α (PPARα), an important metabolism-associated nuclear receptor, to activate PPARα target genes. In addition, liver-specific PPARα overexpression rescued insulin sensitivity and ameliorated hepatic steatosis and inflammation in IRF9 KO mice. Taken together, our results indicate that IRF9 attenuates hepatic insulin resistance, steatosis and inflammation through interaction with PPARα